Spinocerebellar ataxia type 3: subphenotypes in a cohort of brazilian patients - Adriana Moro; Renato P. Munhoz; Walter O. Arruda; Salmo Raskin; Mariana Moscovich; Hélio A.G. Teive (Arquivos de Neuro-Psiquiatria)
Spinocerebellar ataxia type 3 (SCA3) involves cerebellar, pyramidal, extrapyramidal, motor neuron and oculomotor systems with strong phenotypic heterogeneity, that lead us to classify the disorder into different clinical subtypes according to the predominantly affected motor systems. Method The series comprises 167 SCA3 patients belonging to 68 pedigrees, studied from 1989-2013. These patients were categorized into seven different subphenotypes. Results SCA3 cases were clustered according to the predominant clinical features. Three most common forms were subphenotype 2, characterized by ataxia and pyramidal symptom was observed in 67.5%, subphenotype 3 with ataxia and peripheral signs in 13.3%, and subphenotype 6 with pure cerebellar syndrome in 7.2%. Conclusion Our study was the first to systematically classify SCA3 into seven subphenotypes. This classification may be particularly useful for determination of a more specific and direct phenotype/genotype correlation in future studies.